2008
DOI: 10.1080/15419060802014305
|View full text |Cite
|
Sign up to set email alerts
|

Identification of rab20 as a Potential Regulator of Connexin43 Trafficking

Abstract: Connexin oligomerization and trafficking are regulated processes. To identify proteins that control connexin43 (Cx43), a screen was designed using HeLa cells expressing a Cx43 construct with di-lysine endoplasmic reticulum (ER)-retention/retrieval motif, Cx43-HKKSL. At moderate levels of expression, Cx43-HKKSL is retained in the ER as monomers; however, Cx43-HKKSL stably overexpressed by HeLa cells localizes to the perinuclear region and oligomerizes. HeLa/Cx43-HKKSL overexpressors were transiently transfected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 64 publications
2
26
0
Order By: Relevance
“…Importantly, 4-PBA improves the trafficking of several mutant transmembrane proteins, including the ⌬F508 mutant of cystic fibrosis transmembrane regulator (CFTR) (Rubenstein et al, 1997). We found that 4-PBA enhanced the ability of HeLa cells to process overexpressed Cx43 that would otherwise saturate the quality control pathway in these cells Das Sarma et al, 2008). Because 4-PBA alters protein expression, these observations suggested that the ability of 4-PBA to compensate for Cx43 overexpression was because of the increased expression of one or more elements of the connexin quality control pathway.…”
mentioning
confidence: 87%
“…Importantly, 4-PBA improves the trafficking of several mutant transmembrane proteins, including the ⌬F508 mutant of cystic fibrosis transmembrane regulator (CFTR) (Rubenstein et al, 1997). We found that 4-PBA enhanced the ability of HeLa cells to process overexpressed Cx43 that would otherwise saturate the quality control pathway in these cells Das Sarma et al, 2008). Because 4-PBA alters protein expression, these observations suggested that the ability of 4-PBA to compensate for Cx43 overexpression was because of the increased expression of one or more elements of the connexin quality control pathway.…”
mentioning
confidence: 87%
“…The trafficking of Cx43 in monomer form to the TGN is facilitated through interactions with the GTPase protein rab20 (Das Sarma et al, 2008). By use of GST pull-down or yeast-2-hybrid assays, connexins have also been found to specifically interact with consortin within the TGN.…”
Section: A Gap Junction Channelsmentioning
confidence: 99%
“…One such member is Rab20, which is mainly expressed in the apical side of kidney tubule, intestine epithelial cells and non-polarized cells [21], [22]. It is known that Rab20 localizes in the Golgi, ER region and some endocytic compartments, however its function remains uncharacterized [21], [23], [24]. Most recently, it has been shown that Rab20 is recruited to phagolysosomes containing Staphylococcus aureus , whereas it is dissociated from phagosomes containing Mycobacterium tuberculosis , which arrests phagosome maturation [25].…”
Section: Introductionmentioning
confidence: 99%